Analisis Kepercayaan Konsumen terhadap Roti Aoka di Pamarayan (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze consumer trust levels toward Roti Aoka in the Pamarayan region. Roti Aoka, a flagship product of PT Indonesia Bakery Family, is widely known for its affordability (IDR 2,000–IDR 4,000) and good quality. Using a survey questionnaire method with purposive sampling, 100 respondents were selected based on their experience consuming Roti Aoka. The data shows that 97.2% of respondents are familiar with the product, while 98.1% have purchased it. The majority of respondents (81.1%) expressed satisfaction or high satisfaction with the product's quality, taste, and price. However, there is room for improvement, with 39.6% of respondents giving neutral responses regarding quality. This study highlights the importance of flavor innovation, ingredient education, and service enhancement to maintain consumer loyalty.